THE EFFECTIVITY OF ACUPRESSURE THERAPY TO RELIEVE LABOR PAIN DURING THE ACTIVE PHASE OF THE FIRST STAGE - Qothrun Nadaa Hibatulloh (Universitas Airlangga, 2022)
Labor pain is the main issue that happens to women during delivery. In Brazil, labor pain can reach over 50% of the natality rate in a hospital, which is the highest percentage in the world. If labor pain is neglected, mothers can experience depression and distress related to their sexual activity. It will also increase the demand for sectio caesarea delivery. One of the methods to relieve labor pain with no continuous provision of medicine, effective cost, and relatively low risk is acupressure. The objective of this study is to examine the effectiveness of acupressure therapy on relieving labor pain during the Active Phase of the First Stage. This study applied a literature review research method by searching and examining previous journal articles that match the inclusion criteria and exclusion criteria. The journal articles were obtained from the Google Scholar database, ResearchGate, Wiley Online Library, and Elsevier with the keywords Acupressure, Labor Pain or Akupresur, Nyeri Persalinan. From thirteen articles analyzed, nine articles suggest LI4 acupressure point which is placed at metacarpal between the thumb and index finger. The majority of articles claim that severe pain occurs during labor before being intervened. Meanwhile, all articles state that acupressure is effective in relieving labor pain during the Active Phase of the First Stage.